KIPRAH NANOMATERIAL DALAM KEHIDUPAN MANUSIA DAN DAMPAKNYA - Fajaroh, Fauziatul
Padadekadeterakhirinisebagaimanaistilah-istilahberawalannanolainnyaistilahnanomaterialtelahdemikianpopulertidakhanyaterbatasdalamkarya-karyailmiahtetapijugadalamkehidupanbermasyarakat(Pal2011).Halinimembuktikanbahwateknologinanotelahmenjadibagianpentingdarimasyarakat.Bersama-samadengannanosaindannanoteknologiIstilahnanomaterialpertamakalidiperkenalkanolehNorioTaniguchipadatahun1974dalamsuatutulisantentangteknologipenciptaanobyekberskalananometer.Nanometeradalahsuatusatuandalamsisteminternasionalyangmenggambarkanukuransebesar10-9meter.Nanomaterialdigambarkansebagaibahandenganpanjang11000nmdalamsetidak-tidaknyasatudimensinyaNamunumumnyananomaterialdidefinisikansebagaimaterialyangberdiameterdalamkisaran1hingga100nm.DefinisilaintentangnanomaterialmenurutorganisasiInternasionaluntukStandardisasi(ISO)adalahmaterialdengandimensieksternaldalamskalananoataumaterialdenganstrukturinternalataustrukturpermukaandalamskalanano.DefinisidariKomisiEropamenyebutkanbahwananomaterialdapatberupamaterialalamiahinsidentalatausintetisyangmengandungkomponenyangtersusunataspartikelbebasatausebagaiagregatatauaglomeratdimana50%ataulebihdarikomponennyamerupakanpartikelyangmemilikiminimalsatudimensieksternalnyaberadadalamkisaranukuran1100nm(Sudhaetal.2018).Daridefinisidiatasdapatdinyatakantanpakitasadaribahwananomaterialitusendiritelahlahirbersamaandenganpenciptaanalamsemestabesertaisinya(Sudhaetal.2018).NanomaterialdialamamatlahberlimpahbaiksebagaisegmenbiotikmaupunabiotikciptaanAllahSWT.Nanomaterialalamiahdiproduksiolehspesiesbiologisataumelaluiaktivitasantropogenik.Tubuhkitasendiriadalahcontohsempurnadarirakitannanomaterial.Setiapbagiandaritubuhkitadibangundarinanomaterialyangmemilikipengaturanstrukturaltertentuyangberbedasatudenganlainnyasesuaifungsimasing-masing.Fungsi-fungsilogikamemorigeraksintesiskonversienergibahkankesadarandirikitaadalahhasillangsungdarikompleksitasstrukturberskalanano.SebagaicontohDNAyangadadidalamintiselyangikutbertanggungjawabdalamfungsisintesisyangmemilikitugasutamamenyimpandanmereplikasiinformasiadalahmerupakansuatustrukturnano.